TINJAUAN LITERATUR SISTEMATIS: KEMAMPUAN SPASIAL MATEMATIS DALAM PENGEMBANGAN PEMAHAMAN MATEMATIKA DI SEKOLAH DASAR - Nur Siyam, Isnaini; Wiryanto; Endah Budi Rahaju (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematical spatial ability is one of the important cognitive aspects in developingmathematical understanding, especially in the concepts of geometry, algebra, andmeasurement. This systematic literature review aims to evaluate the role andinfluence of spatial ability in mathematics learning in elementary schools. A total of10 studies from various scientific journals published between 2016 and 2024 wereanalyzed to identify the relationship between spatial ability and mathematicsachievement, spatial ability development strategies, and learning media factorsthat greatly determine the success of students' mathematical spatial abilities thataffect this skill. The results of the review indicate that spatial ability is positivelyrelated to mathematics achievement and can be improved through visual andmanipulative-based interventions. In addition, the study also found a relationshipbetween various approaches in implementing learning. This review emphasizesthe importance of integrating spatial activities in mathematics learning inelementary schools to improve students' understanding of complex mathematicalconcepts